Built Environment Ecosystems Framework towards Sustainable Urban Housing Infrastructure. Issue 4 (November 2020) - Dyson, Anna; Keena, Naomi; Organschi, Alan; Gray, Lisa; Novelli, Nick; Bradford, Kipp; Aly-Etman, Mohamed; Gindlesparger, Matt; Wildman, Hind; Duwyn, Jonathan; Otto, Martina; Loran, Sophie; et al.
Abstract: As the rates of urbanization increase to unprecedented levels, the urgent need for sustainable housing and infrastructure has become a widespread global challenge with social, economic and ecological implications. The housing sector directly impacts the majority of the United Nations (UN) Sustainable Development Goals (SGDs). However, striving to achieve these goals in a compartmentalized or siloed manner has impeded the implementation of transformational solutions that increase the security and wellbeing of urban populations. Here, we introduce the Built Environment Ecosystems (BEE) framework, alongside a case study from the Ecological Living Module (ELM) UNEP Program, through an integrated systems approach with synergistic impact. We demonstrate how the multifunctional interlinking of building systems that harness local bioclimatic resources (ie. solar, wind, water, food, agricultural waste, biomaterials) can more viably address a broad spectrum of sustainable development challenges, while increasing local stakeholder agency. We outline how the BEE framework enables the association of SDGs as an integrated package, with an ELM performing as a scalable but Self-reliant Ecosystem of Systems, that could enable systemic change, suggesting the need for further research towards a scale up in the density of such housing systems across multiple climatic and cultural contexts towards ubiquitous sustainable urban housing.